2017
DOI: 10.1007/s00234-017-1884-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of lesions with the MR imaging appearance of multinodular and vacuolating neuronal tumor

Abstract: The natural history of lesions with imaging features of MVNT is overall stable from a clinical and imaging appearance over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 16 publications
7
33
1
Order By: Relevance
“…Since submission of this study, further cases and series have been reported, attesting to the indolent nature of MNVT .…”
Section: Discussionmentioning
confidence: 83%
“…Since submission of this study, further cases and series have been reported, attesting to the indolent nature of MNVT .…”
Section: Discussionmentioning
confidence: 83%
“…MVNTs are of particular interest to the clinician/epileptologist, not only because of the frequent association with epileptic seizures, but also as an operatively treatable cause of epilepsy. A total of 96 cases (including the current case) have been described in the literature to date (Ratilal et al, 2007;Huse et al, 2013;Bodi et al, 2014;Fukushima et al, 2015;Nagaishi et al, 2015;Yamaguchi et al, 2016;Alsufayan et al, 2017;Badat et al, 2017;Cathcart et al, 2017;Gökç e, 2017;Monté et al, 2017;Nunes et al, 2017;Gonzalez-Quarante et al, 2018;Kapucu et al, 2018;Lobo and Srinivasan, 2018;Pekmezci et al, 2018;Thom et al, 2018) (supplementary table 1), of which 37 were histopathologically verified (HV) (38.54%). A slight female predominance was noticed in both non-HV and HV cases (M:F=2:3 and M:F=9:11, respectively).…”
Section: Discussionmentioning
confidence: 96%
“…They have a characteristic “bubbly” cystic appearance with fairly extensive associated T2/FLAIR signal abnormality and minimal enhancement in 20‐30% of cases (Fig ) . MVNT is a more recently characterized benign, mixed glial neuronal lesion consisting of a subcortical cluster of tiny, cystic, nodular lesions with associated T2/FLAIR signal abnormality ( Fig ) . MVNTs are usually seen in the deep cortical ribbon and superficial subcortical white matter in the high convexities .…”
Section: Pathologic Entities Mimicking and Involving Perivascular Spacesmentioning
confidence: 99%
“…[34][35][36] MVNTs are usually seen in the deep cortical ribbon and superficial subcortical white matter in the high convexities. 35 They are associated with seizures in around 30% of patients and rarely show progression or enhancement. 36…”
Section: Neoplastic Cystic Entities Mimicking Perivascular Spacesmentioning
confidence: 99%